Islam dan Dakwah: Dampak Media Sosial terhadap Aktivitas Dakwah di Lingkungan Mahasiswa - Fina Ayu Nurlestari; Kirana Khairunnisa Azhary; Mayang Sari; Raisha Najla Mutia; Indah Sari (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
This study aims to analyze the influence of social media use on the form, intensity, and effectiveness of da'wah activities among students. Da'wah in Islam refers to the effort to convey religious teachings to individuals or groups so that they can understand, feel, and apply these teachings in their lives. This study aims to examine the impact of social media use on the continuity of Islamic da'wah among students, especially when faced with the advancement of digital entertainment today. In addition, this study aims to explore the function of social media as a tool for da'wah, identify emerging opportunities and obstacles, and discuss changes in the way students receive and participate in Islamic da'wah activities in the digital age. This research uses a qualitative approach with a descriptive qualitative type, which aims to analyze the impact of social media on the continuity of da'wah in the student environment. A qualitative approach was chosen because this study focuses on in-depth investigation based on the research subject. Data and information were collected directly from the source to analyze the impact of social media on the sustainability of da'wah among students. The results of the study show that social media has changed the pattern of da'wah among students, both in terms of form and how it is received. Based on interviews, most students believe that da'wah through social media has the potential to have a negative impact if not managed properly, such as the emergence of misunderstandings, superficial messaging, and a tendency to consume religious content instantly. However, social media still has great potential as an effective means of da'wah if used appropriately and responsibly. These findings contribute to contemporary da'wah studies by emphasizing the importance of more critical and targeted management of digital da'wah. Practically, this research implies the need to formulate a more educational, reflective, and student-centered model of social media-based da'wah in the digital age.